(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This Paper looks on various educational loan schemes launched by government for higher education system of India. The higher education shows its maximum growth with a very surprising growth rate especially after independence. Financial assistance is also must for growth of education system of India. As the Indian system have lots of drawbacks in financing and management in terms of its accessibility, importance and its reliability. These drawbacks are now being used as a powerful tool for enhancing the growth of the higher education to the extreme level. It is the primary responsibility of the state to provide the eligible with good quality higher education at reasonable cost. There shall be no withdrawn of the state from this responsibility. Our Government should take more steps towards growth of education system in India, because, education is backbone of our country. There shall be dominant role for genuine academics in the governing structure of higher education institutions. Higher education in india also a great evidence behind the economic growth of india. This paper also shows role of the state in growth of education system. The findings of this paper may be useful for readers to gain more knowledge regarding various loans schemes available in the country.